Avian Communities of Alatish National Park, Ethiopia. (1st February 2022) - Tesfahun, Takele; Ejigu, Dessalegn
Abstract : Alatish National Park, which is located in the Amhara National Regional State at the border with the Republic of Sudan, is rich in its avian resources. To study the park's avian communities, the study area was classified based on its vegetation structures into riverine woodland, wooded grassland, woodland, and bamboo woodland. Data were collected from July 2017 to April 2018 using line transect and point count methods. As a result, 132 species of birds belonging to 18 orders and 55 families were identified. The highest species diversities during the wet (H' = 3.53) and dry (H' = 3.55) seasons were recorded in the riverine woodland habitat. Species evenness was also the highest during the wet ( E  = 0.79) and dry ( E  = 0.77) seasons in the riverine woodland habitat. The bamboo woodland habitat harboured the lowest species diversity during the wet (H' = 2.81) and dry (H' = 2.45) seasons. More species similarity (SI = 0.90) was recorded between wooded grassland and bamboo woodland habitats during the dry season. Relative abundance of birds among the different species showed significant differences ( F 131, 1452 = 2.94, P < 0.05 ), and most birds in the area were identified as uncommon species. Forest fire, logging, and overgrazing by cattle have significantly contributed to habitat destruction in the park which might act as the cause for reduction in avian diversity. Therefore, appropriate conservation strategies should be designed and implemented to minimize avian habitat destruction due to various anthropogenic activities within the park.